PENGEMBANGAN BAHAN AJAR IPS TERPADU BERKARAKTER SMP KELAS VII SEMESTER I - Simanjuntak, Tianna; Idrus, Ali; Muazza, Muazza (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2013)
The use of instructional materials in the learning process in the classroom is paramount for teaching materials is one of the factors that affect the improvement of the quality of learning. Similarly, in the study of Social Sciences (IPS) in the Junior High School (SMP) has some problems, such as: its not integrated teaching materials or teaching social studies mostly still carried out separately. Research aims: (1) describe the product development process of teaching materials such as books of Social Sciences (IPS) integrated characterless, (2) describe the use of an integrated social studies teaching material characterless. Models development of teaching materials using the model of Dick and Carey (1994), while the steps are: (1) set a goal of learning, (2) analysis of learning, (3) identify the child's abilities and characteristics of students, (4) formulate specific goals, (5) developing test items, (6) develop learning strategies, (7) develop and choose the subject matter, (8) to design and conduct formative evaluation, (9) revise the learning. The average acquisition individual trials on the effectiveness of instructional materials is 79%, a small group test the effectiveness of teaching materials is 84.2%. Student pretest value reached 52.5% at the posttest value of 100% or the overall student has achieved the minimum completeness criteria (KKM). While to a large group of placement test, which means 80% proven effective teaching materials. Assessment of two (2) social studies teachers to gain teaching materials with an average value of 87%, as well as to aspects of the content material is very good quality is obtained with a percentage of 86% and design aspects with the percentage 76%. Based on the results of product testing can be concluded that the development of teaching materials based IPS Integrated Character Education classes VII Semester is fit for use and has a level of effectiveness and attractiveness, these teaching materials students can use independently. Keyword: Teaching Material, Integrated Social Science Characterless